Cyclodextrin insulation prevents static quenching of conjugated polymer fluorescence at the single molecule level. - Thomsson, D; Camacho, R; Tian, Y; Yadav, D; Sforazzini, G; Anderson, H; Scheblykin, I (2013)
Conjugated polymers (CPs) are promising materials for fluorescence imaging application. However, a significant problem in this field is the unexplained abnormally low fluorescence brightness (or number of fluorescence photons detected per one excitation photon) exhibited by most of CP single chains in solid polymer hosts. Here it is shown that this detrimental effect can be fully avoided for short chains of polyfluorene-bis-vinylphenylene (PFBV) embedded in a host polymer matrix of PMMA, if the conjugated backbone is insulated by cyclodextrin rings to form a polyrotaxane (PFBV-Rtx). Fluorescence kinetics and quantum yields are measured for the polymers in liquid solutions, pristine films, and solid PMMA blends. The fluorescence brightness of PFBV-Rtx single chains dispersed in a solid PMMA is very close to that expected for a chain with 100% fluorescence quantum yield, while the unprotected PFBV chains of the same length possess 4 times lower brightness. Despite this, the fluorescence decay kinetics are the same for both polymers, suggesting the presence of static or ultrafast fluorescence quenching in the unprotected polymer. About 80% of an unprotected PFBV chain is estimated to be completely quenched. The hypothesis is that the cyclodextrin rings prevent the quenching by working as 'bumpers' reducing the mechanical forces applied by the host polymer to the conjugated backbone and help retaining its conformational freedom. While providing a recipe for making CP fluorescence bright at the single-molecule level, these results identify a lack of fundamental understanding in the community of the influence of the environment on excited states in conjugated materials.